РАЗВИТИЕ ПРАВ КОММЕРСАНТА В ЗАКОНОДАТЕЛЬСТВЕ РЕСПУБЛИКИ МОЛДОВА - Игнатьев, Василий (SUPREMANCE OF LAW, 2017)
In article commerce is analyzed as a type of business, alongside with other adjacent concepts from the point of view of the constitutional maintenance of social justice and other market arguments in conditions of overcoming of financial crisis.